(untitled) (Élisée - Revista de Geografia da UEG, 2021)
ABSTRACT This article aims to discuss the education of rural populations in the Southeastern region of Goiás, analyzing the territorial and historical characteristics of this region for, thus, problematize the current conditions of school education of rural subjects in this context. Taking as a reference the rural education paradigm that, in the last decades, has been presented in opposition to countryside education, the central argument is that both in the past and in the present, formal education for rural populations develops in a hybrid system, with characteristics of the two paradigms. The analyzes brought here are the result of teaching, research and extension actions developed by the authors in municipalities in the Southeastern region of Goiás, in elementary education, graduate and undergraduate programs. Keywords: Rural education. Territory. Southeast Goiás. (Re) existence.